INTERNATIONAL HUMAN RIGHTS (World Bulletin of Management and Law, 2024)
In this article, international human rights documents are discussed in detail, the situations that are happening in the world and have been formed historically, how important it is to protect these rights by the state, and the need to do this through effective ways, and as a result there is talk about the convergence of nations at the international level. The internationally accepted laws on human rights are listed